Vehicle, mechanical and electrical engineering selected, peer reviewed papers from the 2014 International Conference - Fang, Zhigan; Xu, Jianjun; Wang, Pin (Applied Mechanics and Materials, 2015)
Collection of selected, peer reviewed papers from the 2014 International Conference on Vehicle, Mechanical and Electrical Engineering (ICVMEE 2014), November 29-30, 2014, Wuhan, China. The 187 papers are grouped as follows: Chapter 1: Vehicle Engineering and Design; Chapter 2: Traffic and Transport Engineering, Vehicle and Road Safety; Chapter 3: Mechanical and Dynamical Principles and Design, Machinery and Manufacturing Engineering;Chapter 4: System Modeling and Algorithms for Intelligent Automation and Control Systems;Chapter 5: System Test, Diagnosis, Detection and Monitoring, Instrumentation and Measurement, Optimization and Algorithms, Numerical Methods and Simulation